Метафизичность смысла и значения в искусственном интеллекте - Романченко, В. В. (ХНУРЕ, 2020)
The article discusses the philosophical problems of artificial intelligence. The modern approaches to the definition of natural and artificial intelligence are investigated. The non-identity of sense and meaning in the conditions of artificial intelligence is analyzed. A hypothesis is given that the human understanding of meaning depends on intuition and experience and is transcendental. It is it that underlies human understanding and determination of meaning.
Keywords: философия; метафизичность